NT‐proBNP/BNP ratio for prognostication in European Caucasian patients enrolled in a heart failure prevention programme. (29th September 2021) - Sweeney, Claire; Pharithi, Rebabonye B.; Kerr, Brian; Ryan, Cristin; Ryan, Fiona; Collins, Líbhan; Halley, Carmel; Barrett, Matt; Watson, Chris J.; McDonald, Kenneth; Ledwidge, Mark
Abstract: Aims: Guidelines support the role of B‐type natriuretic peptide (BNP) and amino‐terminal pro‐BNP (NT‐proBNP) for risk stratification of patients in programmes to prevent heart failure (HF). Although biologically formed in a 1:1 ratio, the ratio of NT‐proBNP to BNP exhibits wide inter‐individual variability. A report on an Asian population suggests that molar NT‐proBNP/BNP ratio is associated with incident HF. This study aims to determine whether routine, simultaneous evaluation of both BNP and NT‐proBNP is warranted in a European, Caucasian population. Methods and Results: We determined BNP and NT‐proBNP levels for 782 Stage A/B HF patients in the STOP‐HF programme. The clinical, echocardiographic, and biochemical associates of molar NT‐proBNP/BNP ratio were analysed. The primary endpoint was the adjusted association of baseline molar NT‐proBNP/BNP ratio with new‐onset HF and/or progression of left ventricular dysfunction (LVD). We estimated the C‐statistic, integrated discrimination improvement, and the category‐free net reclassification improvement metric for the addition of molar NT‐proBNP/BNP ratio to adjusted models. The median age was 66.6 years [interquartile range (IQR) 59.5–73.1], 371 (47.4%) were female, and median molar NT‐proBNP/BNP ratio was 1.91 (IQR 1.37–2.93). Estimated glomerular filtration rate, systolic blood pressure, left ventricular mass index, and heart rate were associated with NT‐proBNP/BNP ratio in a linear regression model (all P  < 0.05). Over a median follow‐up period of 5 years (IQR 3.4–6.8), 247 (31.5%) patients developed HF or progression of LVD. Log‐transformed NT‐proBNP/BNP ratio is inversely associated with HF and LVD risk when adjusted for age, gender, diabetes, hypertension, vascular disease, obesity, heart rate, number of years of follow‐up, estimated glomerular filtration rate, and baseline NT‐proBNP (odds ratio 0.71, 95% confidence interval 0.55–0.91; P  = 0.008). However, molar NT‐proBNP/BNP ratio did not increase the C‐statistic (Δ −0.01) and net reclassification improvement (0.0035) for prediction of HF and LVD compared with NT‐proBNP or BNP alone. Substitution of NT‐proBNP for BNP in the multivariable model eliminated the association with HF and LVD risk. Conclusions: This study characterized, for the first time in a Caucasian Stage A/B HF population, the relationship between NT‐proBNP/BNP ratio and biological factors and demonstrated an inverse relationship with the future development of HF and LVD. However, this study does not support routine simultaneous BNP and NT‐proBNP measurement in HF prevention programmes amongst European, Caucasian patients.